"Angle to Be Corrected" in Preoperative Evaluation for Hallux Valgus Surgery: Analysis of a New Angular Measurement. (February 2016) - Ortiz, Cristian; Wagner, Pablo; Vela, Omar; Fischman, Daniel; Cavada, Gabriel; Wagner, Emilio
Background: The most common methods for assessing severity of hallux valgus deformity and the effects of an operative procedure are the angular measurements in weightbearing radiographs, specifically the hallux valgus angle and intermetatarsal angle (IMA). Our objective was to analyze the interobserver variability in hallux valgus patients of a new angle called the "angle to be corrected" (ATC), and to compare its capacity to differentiate between different deformities against IMA. Methods: We included 28 symptomatic hallux valgus patients with 48 weightbearing foot x-rays. Three trained observers measured the 1 to 2 IMA and the ATC. We then identified retrospectively 45 hallux valgus patients, which were divided into 3 operative technique groups having used the ATC as reference, and analyzed the capacity of the IMA to differentiate between them. Results: The IMA average value was 13.6 degrees, and there was a significant difference between observer 3 and observer 1 ( P = .001). The average value for the ATC was 8.9 degrees, and there was no difference between observers. Both angles showed a high intraclass correlation. Regarding the capacity to differentiate between operative technique groups, the ATC was different between the 3 operative technique groups analyzed, but the IMA showed differences only between 2. Conclusions: The ATC was at least as reliable as the intermetatarsal angle for hallux valgus angular measurements, showing a high intraclass correlation with no interobserver difference. It can be suggested that the ATC was better than the IMA to stratify hallux valgus patients when deciding between different operative treatments. Level of Evidence: Level III, comparative study.